Saúde e desastres no Brasil: uma reflexão sobre os aspectos envolvidos em eventos hidrológicos e rompimento de barragens - Eliane Lima e Silva; Helen Gurgel; Carlos Machado de Freitas (Confins)
Disasters associated with floods and dam ruptures cause direct and indirect impacts on health and their damages depend on the vulnerability and resilience present in the affected areas. In this paper, we reflect on the sectoral public policies involved in disaster risk management in Brazil, as illustrated by the floods due to the rupture of ore tailings dam at Brumadinho-MG. For this, a bibliographical and documentary survey was carried out in addition to the analysis of data on the occurrence of floods and the registration of dams in Brazil. These are recurrent problems in the country and are distributed throughout the country and, despite having specific public policies, these have not actually been implemented, which puts a large part of the country's population at risk. It can be seen that disasters have become part of the routine of the country and, in some discourses, it is observed until their naturalization, while the most serious are treated as exceptional or unforeseeable. When analysing the Brazilian scenario of floods and dams, it is evident the non-prioritization of preventive actions and the adoption of reactive approaches seems to be part of the strategy of emergency management. It is evident the need to reorganize disaster management, involving its different authors, in order to establish processes that reduce the fragmentation and overlapping of actions. In this context, disaster preparedness and response plans are needed in all municipalities at risk, and cannot be limited to the bureaucratic process of legislation and devoid of warning and alarm systems that effectively contribute to saving lives.